The Aceh Party Across Two Decades of Elections: Political Resilience and Institutional Adaptation - Caroline Paskarina; Ratnia Sholihah; Ari Ganjar Herdiansah; Aryos Nivada (SCAD Independent, 2026)
Over two decades after the Helsinki peace agreement, the Aceh Party has remained a central actor under Aceh's autonomy-based political system; however, its declining electoral performance and limited gender inclusion raise important questions regarding the organizational resilience of post-conflict local parties. This study examined how internal organizational dynamics and external regulatory pressures shaped the party’s adaptation and long-term viability, with particular attention to women’s political representation. Employing a qualitative case study design, the study utilized semi-structured interviews with key political actors and analysts, complemented by documentary analysis of electoral data and regulatory frameworks. The findings indicated that elite fragmentation, limited cadre regeneration, concentration of leadership authority, and regulatory constraints undermined organizational cohesion, while the absence of structured gender-inclusive mechanisms restricted broader societal engagement. The study contended that in post-conflict autonomy settings, the durability of local parties was shaped less by their historical legitimacy and more by regularized institutional renewal, their ability to adapt, and the use of inclusive organizational practices. By integrating organizational, structural, and gender dimensions within a single analytical framework, this study offered a more comprehensive understanding of party durability and provided a basis for future comparative research in post-conflict and autonomy regions. It also highlighted the importance of aligning institutional reform with evolving societal expectations to sustain democratic legitimacy over time.